Analysis of Work Posture on Gambier Farmers Using the Rapid Entire Body Assessment Method - Firdani, Fea; Alfian, Azyyati Ridha; Gusti, Aria; Saputra, Hendra (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 9 No 1 (2023): Volume 9 No 1 Tahun 2023, 2023)
In processing gambier farmers work with various postures, namely standing, sitting, and some in a bent position. This study aims to determine the work posture to assess the ergonomic risk level in gambier processing farmers. This study is an observational study using the Rapid Entire Body Assessment (REBA) method. The survey was conducted in March – July 2022 on gambier processing farmers in Pesisir Selatan Regency, West Sumatra. Work postures were assessed starting from picking gambier leaves, preparing for boiling, boiling, pressing, settling, draining, and printing gambier. There are 11 work postures that were assessed. Data were collected using observations, documentation, and REBA worksheets. Then the data were analyzed based on the score from the REBA table, and the risk score was calculated. The results of the ergonomic risk assessment at each stage of the gambier processing process are it is known that in the process of picking gambier leaves the final score is 10, in the boiling preparation stage there are 4 different work positions with 2 final scores of 6, and 2 final scores 8, then the boiling stage the score final 9, tying gambier leaves for press preparation with a final score of 9, gambier leaf counting with a score of 9, gambier leaf press process with a final score of 9, gambier sap draining process with a final score of 10 and printing process with a final score of 8. Out of 11 postures at the gambier processing stage, nine poses have high risk with a score of 8 to 10, and two positions are of moderate risk. Efforts need to be made to improve equipment for processing gambier to prevent work-related injuries and reduce the physical workload on gambier processing farmers.